Gender, Komisaris Independen, Ukuran Dewan, Komite Audit, dan Pengungkapan Tanggung Jawab Sosial Perusahaan - Anggraeni, Novita (E-Jurnal Akuntansi; Vol 30 No 7 (2020)DO - 10.24843/EJA.2020.v30.i07.p16, 2020)
This research aims to determine the effect of gender, independent commissioners, board size and audit committee on corporate social responsibility disclosure index. Sample used are companies listed on the Global Reporting Index database and listed on the Indonesia Stock Exchange for period 2013-2018, as many as 340 company-years. The sources of the data were taken from annual reports and sustainability reports. This research uses a quantitative approach and data analysis technique used is multiple linear regression analysis. The results shows that the size of the board and audit committee have a positive effect on corporate social responsibility disclosures. Independent commissioners have a negatif effect on corporate social responsibility disclosure, and no evidence of the effect of gender on corporate social responsibility disclosure. Keywords: Corporate Social Responsibility Disclosure; Gender; Independent Commissioners; Board Size; Audit Committee.